Approach to multidrug resistant infections in pediatric transplant recipients - Sara W. Dong; Tanvi S. Sharma; Paul K. Sue (Frontiers Media S.A., 2023)
IntroductionThere is increasing recognition of infections due to multidrug-resistant Gram negative (MDRGN) bacterial infections among children undergoing solid organ and hematopoietic cell transplantation, which may be associated with morbidity and mortality.MethodsWe present two vignettes that highlight the clinical challenges of evaluation, management, and prevention of MDRGN bacterial infections in children prior to and after transplantation. The goal of this discussion is to provide a framework to help develop an approach to evaluation and management of these infections.ResultsSource control remains the utmost priority in management of MDR infections and is paired with antibiotic selection guided by in vitro susceptibilities, adverse effect profiles, and clinical response. Identification and confirmation of resistance can be challenging and often requires additional testing for recognition of complex mechanisms. Current antimicrobial approaches to MDRGN infections include use of novel agents, prolonged infusion, and/or combination therapy. We also discuss preventative efforts including infection control, antimicrobial stewardship, targeted pre-emptive or prophylactic treatment, and decolonization.DiscussionThe impact of MDRGN infections on patient and graft survival highlights the need to optimize treatment and prevention strategies.